2020
DOI: 10.3390/nu12051434
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots Between Inflammatory Bowel Disease and Metabolic Syndrome: A Focus on Gut-Derived Metabolites

Abstract: The role of the microbiome in health and disease has gained considerable attention and shed light on the etiology of complex diseases like inflammatory bowel disease (IBD) and metabolic syndrome (MetS). Since the microorganisms inhabiting the gut can confer either protective or harmful signals, understanding the functional network between the gut microbes and the host provides a comprehensive picture of health and disease status. In IBD, disruption of the gut barrier enhances microbe infiltration into the subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 267 publications
(343 reference statements)
0
48
0
1
Order By: Relevance
“…There are many studies showing that the intestinal microflora and the bacterial metabolites it produces are involved in the metabolic processes in the body. There is also an association between intestinal inflammation and MetS [ 89 ]. Studies carried out in animal models indicate that the presence of microorganisms inhabiting the intestines in the population, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies showing that the intestinal microflora and the bacterial metabolites it produces are involved in the metabolic processes in the body. There is also an association between intestinal inflammation and MetS [ 89 ]. Studies carried out in animal models indicate that the presence of microorganisms inhabiting the intestines in the population, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is a complex ecosystem that plays a critical role in regulation of immune system homeostasis. Recent studies showed that gut microbes are related with many diseases such as obesity, type 2 diabetes, non-alcoholic fatty liver disease, cardiovascular disease, nervous system disease, and IBD [ 3 , 4 , 5 , 6 , 7 ]. It has been reported that dysbiosis of gut microbiota exacerbate the development of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fat composition has been implicated in the development of insulin resistance, including the development of type 2 diabetes, with each type of fat having vastly different effects on insulin resistance and metabolic control (Ikemoto et al ., 1996). Curiously, metabolic abnormalities are increasingly being identified in both human and animal models of colitis (Verdugo-Meza et al ., 2020). We demonstrate that in Muc2 -/- mice that OO and CO diets promote impairments in glucose tolerance, barrier function and alterations to hormone levels leading to metabolic alterations.…”
Section: Discussionmentioning
confidence: 99%